2007
DOI: 10.2527/jas.2006-371
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity of calf- and yearling-fed Brangus steers raised to constant-age and constant-body weight endpoints

Abstract: We tested the hypothesis that fatty acid biosynthesis and adipocyte diameter and volume would be greater in s.c. and i.m. adipose tissues of calf-fed steers than in yearling-fed steers at a constant BW, due to the greater time on feed for the calf-fed steers. Conversely, we predicted that the capacity for s.c. and i.m. preadipocytes to divide, as estimated by 3 H-thymidine incorporation into DNA, would be greater in the less mature adipose tissues of calf-fed steers and in yearling-fed steers at 16 mo of age t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…These results are in agreement with the data of the literature suggesting that subcutaneous adipose tissue is the primary site of fatty acid biosynthesis in cattle (Smith et al, 2007).…”
Section: Discussionsupporting
confidence: 93%
“…These results are in agreement with the data of the literature suggesting that subcutaneous adipose tissue is the primary site of fatty acid biosynthesis in cattle (Smith et al, 2007).…”
Section: Discussionsupporting
confidence: 93%
“…In the BF, the adipocyte numbers of cells less than 35 μm in diameter were higher in heifers fed free choice than those provided the TMR. Furthermore, cell counts were lower in BF than in the PCD possibly because only cells less than 35 μm were counted, however, Smith et al (2007), enumerated total cells in both subcutaneous and intramuscular tissue, cells, they report lower cell numbers, but of larger volume, in subcutaneous than in muscle of steers in agreement with our observations. In the PCD, adipocyte numbers were not affected (P = 0.393) by treatment when determined per mg of dissected fat or mg tissue, but feed withdrawal within both dietary management treatments, although non-significantly (P = 0.96), consistently increased the number of cells per mg of PCD.…”
Section: Adipocyte Number and Average Cell Sizesupporting
confidence: 90%
“…However, these cattle had been provided a high concentrate diet from weaning and were older than our cattle at slaughter, which could have affected the ultimate adipocyte sizes. Similarly, Smith et al (2007) report larger cell volumes than we were able to count, but found cells with substantially lower cell volumes (575 pL) for intramuscular adipocytes from cattle that were fed finishing diets after they were yearlings as opposed to those fed the same diets from weaning (1157 pL). In the present study the finishing diets were initiated after the heifers were of yearling age and the duration of the finishing diet lasted only 75 d as opposed to the 93 d employed by Smith et al (2007) thus it is expected that, although only cells less than 35 μm in diameter were enumerated, those that would be affected by the feed withdrawal intervention were counted.…”
Section: Adipocyte Number and Average Cell Sizementioning
confidence: 46%
See 1 more Smart Citation
“…In calf production systems, cattle enter the feedlot immediately after weaning at 6–8 mo of age and are fed a high-energy finishing diet ad libitum until slaughter at 12–14 mo of age to take advantage of the faster growth of large-framed cattle [1,2]. On the contrary, in yearling production systems cattle graze pasture and/or crop residues post-weaning prior to entering a feedlot at 15–18 mo of age to allow for growth of frame in small- to medium-framed cattle and takes advantage of lower priced forages and subsequent compensatory growth in the feedlot.…”
Section: Introductionmentioning
confidence: 99%